Identifying ideas through SCAMPER techniques for Examination Invigilation Management Systems (ExIMS) / Sharifah Sarimah Syed Abdullah ... [et al.] - Syed Abdullah, Sharifah Sarimah; Samsudin, Norshuhada; Wan Mohd Rosly, Wan Nur Shaziayani; Othman, Jamal; Hamat, Muniroh; Mazeni, Noor Azizah; Zahari, Mohd Fahmi (Unit Penerbitan JSKM, 2022)
The SCAMPER technique is a productive and versatile technique for generating innovation ideas for product or service. The purpose of the study was to implement the SCAMPER technique into the examination system at the UiTM Penang Branch's Examination Unit. This study demonstrates how the SCAMPER technique ideas can be used to examine an offering from seven different perspectives. The SCAMPER technique was preferred, firstly because it basically aims to create numerous ideas which is expected from divergent thinking process. Second, although there have so many studies about creative thinking strategies in creative literature, there are only a few studies about teaching creativity via SCAMPER. Third, SCAMPER provides an enjoyable environment for thinking creatively. Also, this study attempts to propose improvements in the smoothness of the process. The SCAMPER technique was found to be useful as an idea for determining users' requirements regarding the examination duties exchanged among invigilators in this study. Therefore, the SCAMPER technique is very helpful in ensuring that the Examination Invigilation Management Systems (ExIMS), saves a lot of time.